Integrative Body-Mind-Spirit Social Work : an Empirically Based Approach to Assessment and Treatment - Lee, Mo Yee (Oxford University Press, 2009)
In recent years, interest in non-Western curative techniques among Americans has grown by leaps and bounds. Integrative Body-Mind-Spirit Social Work is the first book to strongly connect Western therapeutic techniques with Eastern philosophy and practices, while also providing a comprehensive and pragmatic agenda for social work, and mental health professionals. This breakthrough text, written by a cast of highly regarded researchers from both Asia and America, presents aholistic, therapeutic approach that ties Eastern philosophy and practical techniques to Western forms of therapy in order to help bring about positive, transformative changes in individuals and families. Integrative therapy focuses on the mind-body-spirit relationship, recognizes spirituality as a fundamental domain of human existence, acknowledges and utilizes the mind's power as well as the body's, and reaches beyond self-actualization or symptom reduction to broaden a perception of self that connects individuals to a larger sense of themselves and to their communities. Here, the authors provide a pragmatic, step-by-step description of assessment and treatment techniques that employ anintegrative, holistic perspective. They begin by establishing the conceptual framework of integrative body-mind-spirit social work, then expertly describe, step-by-step, assessment and treatment techniques that utilize integrative and holistic perspectives. Several case studies demonstrate the approach inaction, such as one with breast cancer patients who participated in body-mind-spirit and social support groups and another in which trauma survivors used meditation to get onto a path of healing. These examples provide solid empirical evidence that integrative body-mind-spirit social work is indeed a practical therapeutic approach in bringing about tangible changes in clients. The authors also discuss ethical issues and give tips for learning integrative body-mind-spirit social work. Professionals in social work, psychology, counseling, and nursing, as well as graduate students in courses on integral, alternative, or complementary clinical practice will find this a much-needed resource that complements the growing interest in alternatives to traditional Western psychotherapy.